BATAS USIA PERKAWINAN DALAM PANDANGAN ULAMA KLASIK DAN KONTEMPORER (Studi Analisis Praktik Perkawinan Dibawah Umur Masyarakat Kampung Nelayan Desa Saletreng Kabupaten Situbondo) - Musdhalifah Musdhalifah; Syamsuri Syamsuri (JURNAL HAKAM, 2022)
Islam does not regulate the age of marriage. Explanations of the minimum age limit for a person to marry are not found in the Qur'an, Sunnah, or the books of classical jurisprudence. The minimum age limit for marriage is only found in some regulations (al-qanun) in countries where the population is Muslim. In Indonesia, the minimum age of marriage is regulated in Law No. 1 of 1974 Article 7 Paragraph 1 and article 15 paragraphs (1) and (2) of the Compilation of Islamic Law. The law has the binding power to be obeyed by all citizens. In reality, there is a waiver of the minimum age limit by the Act. In some community groups, such as the Kampung Nelayan community in Saletreng Village, Situbondo Regency, this neglect still occurs with the rampant practice of marriage at an early age. Based on the results of this study, the practice of underage marriage was carried out for economic reasons. The presence of new members in the family is believed to help ease family work and can have an impact on strengthening the family economy. This practice became widespread because it was supported by the availability of access to manipulation of age data on brides-to-be by related parties.